Desafios da equidade de gênero na área tributária: a representatividade de mulheres nas mais altas posições em organizações brasileiras - Nery, Fernanda Cândido Siegmann (Universidade do Vale do Rio dos Sinos, 2022)
Unconscious biases, based on prejudicesand stereotypes, form invisible barriers that make it difficult for women to advance in corporations. Unconscious biases are not intentional, but they harm women's careers and reduce the chance of gender equity. The present study seeks to elucidate the challenges for gender equality in the tax area in Brazil and which are the biases of organizations to be overcome so that, together with the creation of goals, policies, actions and an inclusive environment, it is possible to reduce obstacles for women working in the tax area so that they reach the highest leadership positions. To this end, interviews were carried out with five women already in the position of director, head of tax or partner of Big Four companies, in order to understand the process of professional growth of these managers in the tax area and to verify common elements in the trajectories of these professionals, as well as by reviewing the literature on the subject, comparing the results of the interviews with what is in the specialized literature so far. In addition, a workshop was held with the objective of designing solutions to minimize the challenges and boost women's leadership in the tax area based on the perception of the participating women. Six women of different levels of seniority participated in the workshop. A highlight regarding the research results is that even the interviewees do not consider that there is a stereotype as “think manager, think male” in the tax area, they report that they perceive isolation in the work environment, in which they are the “only”, in meeting rooms, for example, as a major difficulty in their day-to-day. This is because although there are already many women in the tax area, including managers and directors, in the corporate environment in general, this is not the rule, perpetuating microaggressions. In the workshop it became clear that the imposter syndrome is still an obstacle for women, as well as the fallacy of “having to take care of everything”. On the other hand, actions were suggested such as setting goals for leaders, with the respective dissemination of results, as well as training and workshops to develop women's leadership skills, including self-knowledge and self-confidence.
Keywords: Viés de gênero; Estereótipos; Liderança; Área tributária; Gender bias; Stereotypes; Leadership; Tax area; ACCNPQ::Ciências Sociais Aplicadas::Administração